Electro-optically tunable acoustic switch based on piezoelectric superlattices - Tang, Zhenghua; Lei, Dajun; Huang, Jianquan; Chen, Yaqi (Frontiers in Physics, 2025)
We propose a novel acoustic switch based on piezoelectric superlattices that is tunable by an external direct-current electric field. Our design harnesses the intrinsic coupling between acoustic waves and the oscillations of electric dipole moments within piezoelectric domains, which concurrently generate electromagnetic waves. The periodic modulation of the piezoelectric coefficient folds the phonon dispersion, leading to the intersection and hybridization with the electromagnetic dispersion branch and thereby opening a polaritonic band gap that governs acoustic wave propagation. Numerical simulations reveal that the absolute bandwidth of the first band gap near 10 GHz increases continuously from 0.003 GHz to 0.9 GHz as the electric field is raised from 0 V/m to 1.343 × 106 V/m. Compared with previous acoustic switches, which rely on phase transformations, nonlinear deformations, or radiation pressure, the proposed device operates at much higher frequencies, features continuous and reversible tunability via the electro-optic effect, and benefits from a compact design. Moreover, the observed consistency between the band gaps for acoustic and electromagnetic waves confirms the dual control capability of the switch. These features make the proposed acoustic switch promising for high-frequency acoustic modulation and integrated microwave filtering applications.